Fuzzy EOQ models with ramp type demand rate, partial backlogging and time dependent deterioration rate. (1st January 2012) - Kumar, Ravi Shankar; De, S.K.; Goswami, A.
In this study, a fuzzy inventory model has been discussed for two cases model start with no shortages model start with shortages. Demand rate is of three folded ramp-type time dependent, deterioration rate of the item is time dependent(Weibull) and shortages are partially backlogged. For real situation, we have assumed the backlogging rate and all the cost coefficients as trapezoidal fuzzy number and defuzzification is made with the help of Function Principle and Graded Mean Integration Representation (GMIR) method. Finally using calculus, we have optimised the total cost function. The solution procedure is illustrated with the help of numerical examples.